2018
DOI: 10.3389/fevo.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Modulation of Reunion Behavior in Short and Long Term Marmoset Pairs

Abstract: One major neurobiological substrate regulating social processes is dopamine (DA). DA is implicated in social behavior in species as diverse as fish and birds, and has an established role in regulating relationships between mates in socially monogamous rodents. Marmoset monkeys display traits associated with social monogamy including high rates of affiliation, biparental care, distress upon separation, and aggression toward strangers; several of these behavioral patterns change throughout the development of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Siganid rabbitfishes [19]) and allogrooming (e.g. common marmosets [20]). Affiliative behaviours are often reciprocated between partners and provide mutual fitness benefits, including mate and offspring guarding/provisioning and assisted resource defence [21].…”
Section: Pair Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…Siganid rabbitfishes [19]) and allogrooming (e.g. common marmosets [20]). Affiliative behaviours are often reciprocated between partners and provide mutual fitness benefits, including mate and offspring guarding/provisioning and assisted resource defence [21].…”
Section: Pair Bondingmentioning
confidence: 99%
“…After pair bonds have been established, D1R density in the nucleus accumbens increases, likely inhibiting the formation of new partnerships [44]. Similarly, in common marmosets, D2Rs regulate partner proximity behaviour in new pairs, whereas D1Rs do so in long-term pairs [20]. In zebra finches, dopamine levels in the brain increase with pair bond formation [48] and decrease with pair bond maintenance [49].…”
Section: (Ii) Signalling Molecules and Genesmentioning
confidence: 99%
“…Second, this study provides an important stepping stone between the well-documented role of the DA system in rodent models of social monogamy and the less understood role of DA in regulating nonhuman and human primate social behavior. While previous research has found similarities in the way in which the DA system regulates social interest and behavior between primates and rodents [16,17], the current study highlights the potential for the DA system to function differently in primates than in prairie voles in regulating social interactions. This lack of specialization in the DA system may underlie the behavioral flexibility that is characteristic of both marmoset and human social relationships.…”
Section: Discussionmentioning
confidence: 45%
“…This pattern is not observed when females in short term pairs receive treatment manipulating the D1R. However, when female marmosets from long term pairs receive manipulation (agonist or antagonist) of the D1R, the pair displays reduced proximity behavior during reunion compared to when males receive the same treatment, while proximity behavior patterns during reunion are unaffected by manipulation of the D2R [17]. Together, this set of findings suggests that the distinct roles of the D1Rs in mediating maintenance of attachment, and D2Rs in regulating formation of attachments in socially monogamous primate behavior may be conserved from rodents to primates.…”
Section: Introductionmentioning
confidence: 85%